A state of the art review on the novel mediator asprosin in the metabolic syndrome - Luís, Carla (2020)
Metabolic syndrome is a complex and heterogeneous pathology characterized by a cluster of biochemical, clinical, and metabolic factors that came together in raising the risk of cardiovascular diseases, type 2 diabetes mellitus, and all-cause mortality. Some of these features are well defined in this syndrome like: obesity, inflammation, hypertension, insulin resistance, atherosclerotic dyslipidemias, endothelial dysfunction, and inflammation. This circuit is intermediated by a complex network of hormones, cytokines, transcription factors, and adipokines, among others. Some like leptin, adiponectin, Plasminogen activator inhibitor-1, interleukin-6, Tumor necrosis factor, and their influence on the metabolic syndrome are well described in the literature and new players are described continuously. One novel player was described in 2016 by Romere et al as a fasting-induced glycogenic protein hormone named asprosin.